2014
DOI: 10.1007/s40328-014-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

“Attribute based Inversion” a tool for reservoir characterization: a case study-Kalol Field, Cambay Basin, India

Abstract: With major oil and gas discoveries diminishing in number, industry is turning its attention to redevelop fields with reservoirs (Res) like silts which have otherwise been accorded lower priority earlier. It has always been a challenge to identify the locales with better Re facies development in un-drilled areas of a field and most often many development wells either go dry or turn out to be poor producers, significantly increasing the cost of production from a given field. Kalol Field, Cambay Basin, India is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…All the petrophysical analysis logs, PHI, and Sw logs are upscaled in the structural grid. In a similar approach, the discrete facies logs are also upscaled using 'most of' (a geostatistical algorithm) within the structural grid [16,17]. It is observed that RMS greater than 1 corresponds to reservoir facies at the well location.…”
Section: Facies Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…All the petrophysical analysis logs, PHI, and Sw logs are upscaled in the structural grid. In a similar approach, the discrete facies logs are also upscaled using 'most of' (a geostatistical algorithm) within the structural grid [16,17]. It is observed that RMS greater than 1 corresponds to reservoir facies at the well location.…”
Section: Facies Modellingmentioning
confidence: 99%
“…The upscaled porosity and water saturation logs are populated in the reservoir facies through geostatistical analysis (Kriging Interpolation). In the non-reservoir segment of the facies model, zero porosity and 100% water saturation are assigned during property distribution [16,17]. Fig.…”
Section: Property Modelingmentioning
confidence: 99%